Pengembangan Sistem Pendukung Keputusan Permohonan Kredit Pada Koperasi Universitas Atma Jaya Makassar - Tungadi, Astrid Lestari (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2014)
This paper focuses on the design of development decision support systems credit application in cooperative Universitas Atma Jaya Makassar. Where the current system is currentlyexperiencing a lot of problems in the process of verifying the pleading file members. The verification process involves a lot of data files are still in the form of paper documents sosusceptible to human error in data processing. This paper used a structured design, program PHP, MySQL as the data storage, and DB Designer as an analytical tool. Therefore, this study was conducted with the aim of designing a system that can help the processing of the data file members who apply for credit and designing a credit application decision support systems in cooperative Universitas Atma Jaya Makassar.Keywords : decision support system, credit application, structured design